Investigating Students Understanding in Covid-19 Pandemic through Youtube Video as a Learning Media - Febrianti, Mariska; Banat, Azizatul (International Journal of Language Teaching and Education, 2022)
The aim of this paper is to investigate how is sport students’ in Dehasen University understanding toward learning Bahasa Inggris Profesi using YouTube. This paper used a quantitative approach by using a survey method. The object of this study is sport students in University of Dehasen Bengkulu. The sample of this study is 105 students which learn English by online learning. The teacher applies video in YouTube as material besides using Modul Bahasa Inggris Profesi in learning process. The data collection technique used percentage by the students’ answer of questionnaire in google form. The conclusion showed that sports students can improve their understanding in learning English by watching video in YouTube and also read Modul Bahasa Inggris Profesi. It can be seen from the percentage of each questions in questionnaire and also from the result of student learning in Middle Examination and Final Examination. Although students live in remote area, they still can access the video on YouTubes and gc by their smartphone because the schedule of online learning of English Subject flexible. Keywords: Online learning, Sport Students, English Subject.